Ultrasonography of the nuchal translucency of healthy and abnormal English Bulldog fetuses - Pavan, Leticia [UNESP] (2021)
The aim of this study was to measure the nuchal translucency (NT) of canine fetuses to establish reference values for healthy gestational processes and to verify its effectiveness in the diagnosis of congenital abnormalities. On day 34 of gestation, the NT of three fetuses from each of the 26 English bulldog female dogs was measured. The first fetus was the one located immediately cranial to the bladder, the second was selected from the left side of the abdomen, and the third from the right side. The reference values for healthy animals were offset using descriptive statistics. The diagnostic ability of the test to identify fetal malformations was studied using receiver operating characteristic curve analysis. Of the 26 litters, only 18 had healthy fetuses, 4 had fetuses with anasarca, 3 had fetuses with abdominal wall defects, and 1 had both types of abnormalities. The NT was higher in canine fetuses that presented anasarca in the litter than in normal litters (1.8 +/- 0.77 mm vs. 1.4 +/- 0.48 mm; P = 0.0249), with a cut-off value of NT > 1.45 mm (sensitivity = 61.54%, specificity = 70.18%). NT greater than 1.45 mm seems to be a diagnostic tool for the identification of anasarca during gestation of bulldogs. Considering the unprecedented use of this parameter in canine species and the limitations found during the study, further studies will be needed in order to use it on clinical practice.